Vibegron for the treatment of overactive bladder: a comprehensive update. (2nd September 2022) - Gleicher, Stephanie; Sebesta, Elisabeth M.; Reynolds, W. Stuart; Dmochowski, Roger
ABSTRACT: Introduction: Overactive bladder (OAB) is associated with physical, emotional, and financial burden. After failed conservative measures, second-line therapy includes medications, such as antimuscarinics and beta-3 adrenergic receptor (β3AR) agonists. Antimuscarinics are most commonly prescribed but have systemic side effects that lead to poor compliance. β3AR agonists include mirabegron and vibegron. Mirabegron is a first-generation β3AR agonist that is effective for frequency, urgency urinary incontinence (UUI) and urgency, but has interactions with cytochrome P450 enzymes (CYPs) and cardiovascular sequelae. Vibegron is a second-generation β3AR agonist that is highly selective and does not interact with CYPs. It is effective for reducing UUI episodes and daily micturition number and has a favorable side effect profile. Areas covered: Clinical background, pharmacology, and clinical studies for vibegron. Expert opinion: Vibegron is a welcomed addition to the OAB therapeutic landscape. This single dose, once daily option is effective, especially for patients with wet OAB, with a favorable side effect profile. Sub-analyses of patients ≥ 65 years have shown continued efficacy and safety. The few drug interactions are of benefit, especially for older patients with polypharmacy. As long-term data accrues, vibegron has the potential to drive the OAB therapeutic market.